Pengaruh Penyuluhan Mobilisasi Dini Terhadap Pengetahuan Pelaksanaan Mobilisasi Dini Pada Pasien Post Operasi Di BLUD RSUD H. Padjonga Daeng. Ngallekabupaten Takalar - Dewiyanti Dewiyanti; Wirda Wirda; Suardi Suardi; Dina Oktaviana; Alwi Alwi (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2022)
Background : Early mobilization has a role in the healing process of postoperative patients. One of the nurse's roles in the recovery process is as an educator. Purpose : of the study was to determine the effect of early mobilization counseling on knowledge of the implementation of early mobilization in postoperative patients at the BLUD RSUD H. Padjonga Daeng Ngalle, Takalar Regency. Methods: pre experimental design with a one group pre post test design with the sampling technique used is accidental sampling with a total of 34 respondents. Results: using the Wicoxon test, the calculated value was obtained with a value of = 0.000 <0.05. Conclusion: there is an effect of early mobilization counseling on knowledge of the implementation of early mobilization in postoperative patients at the BLUD RSUD H. PadjongaDaengNgalle, Takalar Regency.